A NATURAL TOUCH IN FASHION: STEAM ECOPRINTS WITH LEAVES AND FLOWERS at SMP NEGERI 6 BANDA ACEH - Zahara, Meutia; Helmanda, Cut Mawar; Nazariah, Nazariah; Anshari, Badrun Al; Ikhsan, Muhammad (Universitas Muhammadiyah Aceh, 2025)
The Community Service Program (PKM) titled